The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/17588928.2013.869740
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in processing of architectural ranking: Evidence from an event-related potential study

Abstract: Visual object identification is modulated by perceptual experience. In a cross-cultural ERP study we investigated whether cultural expertise determines how buildings that vary in their ranking between high and low according to the Western architectural decorum are perceived. Two groups of German and Chinese participants performed an object classification task in which high- and low-ranking Western buildings had to be discriminated from everyday life objects. ERP results indicate that an early stage of visual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Taking the framed-line test as an example, Japanese participants were better in copying the relative length of the lines, but had the disadvantage in copying the absolute length of the lines [4]. A recent cross-cultural ERP study provides evidence consistent with this argument [22]. 'Holistic' thought includes 'attention to relationship' as its core feature.…”
Section: Discussionmentioning
confidence: 86%
“…Taking the framed-line test as an example, Japanese participants were better in copying the relative length of the lines, but had the disadvantage in copying the absolute length of the lines [4]. A recent cross-cultural ERP study provides evidence consistent with this argument [22]. 'Holistic' thought includes 'attention to relationship' as its core feature.…”
Section: Discussionmentioning
confidence: 86%
“…The researchers posited that the N300 response corresponded to the classification of semantic judgment, whereas the N400 response reflected the degree of semantic congruence. Mecklinger, Kriukova, Muhlmann, and Grunwald (2014) researched the cognitive differences in understanding architectural styles between European and Chinese participants. They chose different European architectural styles as their experimental materials based on categorization.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors generally agree with this 'perceptualist' idea that aesthetic impressions are based on the visual processing of elementary and structural stimulus features (Di Dio, Macaluso, & Rizzolatti, 2007;Gregory, Harris, Heard, & Rose, 1995;Ramachandran & Hirstein, 1999;Redies, 2007;Redies, Hasenstein, & Denzler, 2007;Spehar, Clifford, Newell, & Taylor, 2003;Vartanian et al, 2013;Zeki, 1999). More specifically, neuroimaging and electrophysiological studies identified various cortical and sub-cortical areas that are involved in the visual processing and ratings of architectural objects (Aguirre, Zarahn, & D'Esposito, 1998;Epstein & Kanwisher, 1998;Ishai, Ungerleider, Martin, Schouten, & Haxby, 1999;Mecklinger, Kriukova, Mühlmann, & Grunwald, 2014;Oppenheim et al, 2010). Numerous studies indicated that even simple visual features can induce elementary implicit (expressive) meanings of visual objects: for instance, oblique lines induce impression of dynamics, red color induces impression of warmth, etc.…”
mentioning
confidence: 99%